A manager's guide to coaching : simple and effective ways to get the best out of your employees - Emerson, Brian, 1967- (AMACOM/American Management Association, 2008)
It provides specific, powerful questions to ask when coaching and motivating employees to peak performance, and supplies sample conversations, responses, and different ways you can follow up on them."--Jacket